Current auxiliary hot-stamping of advanced high-strength steel and experimental evaluation. Issue 3 (11th February 2017) - Yang, J. L.; Wang, G. F.; Li, X.; Wu, X. S.
Abstract : This paper investigated the influence of electric pulses on the microstructure evolution and mechanical property of hot-stamping process of DP1180. The thickness distribution and absorbed energy of the forming parts were also calculated. The results showed that dynamic recrystallisation occurs in the middle zone in the current auxiliary tension. Moreover, the current would bypass the microcrack. The current auxiliary hot-stamping can be carried out with a current density of 9.7–10.4 A mm −2, thickness distribution formed at 10.4 A mm −2 has the lowest fluctuation of thickness with thinnest rate of 18.7% in middle. The tensile-strength decreased with increasing the current density from 9.7 to 10.4 A mm −2 while elongation increased and the absorbed energy can reached 28.39 kJ at current density of 10.0 A mm −2 .